Systematic longevity risk in social security plans - Cardoso, Mainara de Paula Simões (2023)
The phenomenon of longevity risk permeates the structural framework of the Brazilian pension system and is defined as the probability of pension plan participants surpassing their projected life expectancies. This research paper is primarily concerned with quantifying the influence of longevity risk on the financial stability of pension plans offering lifelong benefits. A model was developed using the Python programming language, employing the Monte Carlo Simulation method to unveil the probability distributions of mathematical provisions across various sample sizes. A comprehensive examination of the empirical findings has led to the deduction that both the coefficient of variation and the contingency loading rate exhibit a consistent decreasing trend, asymptotically approaching zero as the size of the beneficiary population increases. Nevertheless, the inclusion of systematic longevity risk gives rise to an alternative scenario, wherein risk reduction reaches a threshold, resulting in minimal reductions among groups comprising 5,000 to 50,000 policyholders.